SECURE AND SELECTIVE: A FRAMEWORK FOR A CENTRALIZED FEDERAL IDENTITY SYSTEM WITH SCOPE-LIMITED INFORMATION SHARING - Venkata Naga Mahesh Kumar Vankayala (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article proposes a novel approach to digital identity management by implementing a centralized federal identity system. The current practice of manually entering sensitive information across multiple platforms poses significant privacy and security risks. Our proposed system addresses these concerns by securely storing citizens' identities and implementing a granular, scope-limited information-sharing mechanism. The system minimizes data exposure and reduces the risk of identity theft by allowing users to authorize access to only the specific information required for each interaction. We present the architecture of this system, including secure data storage, encryption methods, and purpose-based information-sharing protocols. The benefits of enhanced privacy protection, improved security, and streamlined user experience are discussed alongside potential implementation challenges such as scalability, legal considerations, and public trust. This centralized approach represents a significant step forward in modernizing identity verification for the digital age through comparative analysis with similar systems in other countries and consideration of emerging technologies. Our findings suggest that such a system could mitigate current vulnerabilities in identity management while providing a more efficient and user-friendly verification process across various platforms.